Correction: Macovei et al. Changes in Dento-Facial Morphology Induced by Wind Instruments, in Professional Musicians and Physical Exercises That Can Prevent or Improve Them—A Systematic Review. Life 2023, 13, 1528 - Georgiana Macovei; Raluca Minea; Iarina Teodora Dumitraș; Cosmin Andrei Precup; Liliana Baroiu; Alexandru Nechifor; Adina Oana Armencia; Ana Cristina Lese (Life)
Following publication, concerns were raised regarding the relevance of references [36,37,53] in this publication [...]